CLINICAL PROFILE OF THE PREMONITORY PHASE OF MIGRAINE AMONG THE PATIENTS AT NEUROLOGY DEPARTMENT OF A TERTIARY CARE HOSPITAL OF PAKISTAN - Saeed Arif (Army Medical College Rawalpindi, 2019)
Objective: To assess the clinical profile of the premonitory phase of migraine among the patients presenting with acute attack of migraine at a neurology unit of a tertiary care teaching hospital of Pakistan.